Praca społeczna w diecezji kieleckiej w świetle publikacji na łamach „Kieleckiego Przeglądu Diecezjalnego” w latach 1926-1939. Zarys przemian - Bujak, Grzegorz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The author discusses the most important publications on social issues published in the monthly journal Kielecki Przegląd Diecezjalny in the years 1926-1939. The paper presents the changes that took place in the attitude of the priests to these issues. It demonstrates the process of creating local solutions in this sphere and gradual transition from them to a nationwide vision of the Church, based on a holistic approach to social issues such as the Catholic Action.